BNOS 2016 Abstracts: Poster Presentations - Nandhabalan, Dr Meera (Neuro Oncol, 2017)
Paediatric glioblastomas (pGBM) are biologically distinct from adults, and are in part defined by highly recurrent mutations in the H3F3A gene which encodes the histone variant H3.3. This causes amino acid substitutions at or close to the residues K27 and K36 whose methylation is key to the regulation of transcription. We found that these subgroups have distinct age of incidence, anatomical location, and clinical outcomes. Specifically, through differential binding of the activating mark trimethylated H3K36me3, the G34 mutation causes upregulation of MYCN, a known oncogenic driver in other paediatric diseases. These tumours were mutually exclusive of those harbouring gene amplification of MYCN, which represent a distinct subgroup of pGBM by methylation profiling. Increased copies of MYC/MYCN occur via complex rearrangements on chromosomes 2 and 8, often co-amplifying ID2, PVT1 and other genes. MYC/MYCN amplifications are observed in 13/851 (1.5%) and 36/851 (4.2%) pHGGs respectively and correlate with poorer survival (p<0.0485). These tumours are most common in children peaking at an age of 5.4 years, thus appearing to define a specific subset of paediatric glioblastoma. A synthetic lethality kinome screen in vitro identified H3.3G34 cells to be differentially sensitive to checkpoint kinase 1 inhibition, known to interfere with the stabilisation of MYCN protein. Screening a panel of pGBM cell lines and primary cultures with a series of CHK1 inhibitors (AZD7762, LY2603618, CCT244747) demonstrated a dose-dependent degradation of MYC/MYCN protein which correlated with in vitro GI50 values. Transduction of pGBM cells with stabilised MYCN (T58A) lead to enhanced sensitivity to CHK1 inhibition in both cell viability and clonogenic assays. Combining CHK1 inhibitors with temozolomide produced significant synergy in cells whose resistance is both independent and dependent on MGMT, resulting in combination indices of 0.3–0.6. These data identify a significant proportion of pGBM to be amenable to CHK1 inhibition by virtue of MYC/MYCN dependency. In addition, CHK1 inhibition may play a role in chemosensitisation of paediatric glioblastoma cells to temozolomide regardless of mechanism of alkylating agent resistance. Therefore, combining temozolomide with CHK1 inhibition may be of particular therapeutic benefit in patients whose tumours amplify and/or express MYC/MYCN.